2012
DOI: 10.1021/es302832z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solubilization and Desorption of Organochlorine Pesticides (OCPs) from Soil by Oil-Swollen Micelles Formed with a Nonionic Surfactant

Abstract: The effect of oil-swollen micelles formed with nonionic surfactant polyoxyethylene sorbitan monooleate (Tween 80), cosurfactant 1-pentanol, and linseed oil on the solubilization and desorption of organochlorine pesticides (OCPs) including DDT and γ-HCH from both loam soil and clay soil were investigated. Results showed that the solubilizing capacities of oil-swollen micelles were dependent on the critical micelle concentration (CMC) of Tween 80. Once the concentrations of oil-swollen micelles exceeded the CMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…A less rapid fraction was observed for the 150 and 400 mg L ¡1 amendments as compared to the 700 mg L ¡1 amendment. The values of k slow were two to three orders of magnitude lower than the k rap values for all PAHs in different samples, which is consistent with other studies that apply the two-compartment desorption model [42,48,54]. These results could be considered to well validate the biphasic behaviour of organic compounds desorption and to confirm the supposition of the model.…”
Section: Desorption Ratessupporting
confidence: 89%
“…A less rapid fraction was observed for the 150 and 400 mg L ¡1 amendments as compared to the 700 mg L ¡1 amendment. The values of k slow were two to three orders of magnitude lower than the k rap values for all PAHs in different samples, which is consistent with other studies that apply the two-compartment desorption model [42,48,54]. These results could be considered to well validate the biphasic behaviour of organic compounds desorption and to confirm the supposition of the model.…”
Section: Desorption Ratessupporting
confidence: 89%
“…Error bars represent standard deviation of triplicates previous herbicide study also reported that sorption usually increased with longer residence time in soil (Mamy and Barriuso 2007). Similarly, Zheng et al (2012) mentioned that organochlorine pesticides were sorbed strongly and long-lastingly to soils and sediments.…”
Section: Desorption Of Aged Soilsmentioning
confidence: 86%
“…A microemulsion precursor containing surfactant, alcohol, and oil was prepared by weighing and mixing 14.00 g of polyoxyethylene sorbitan monooleate (Tween 80), 4.60 g of 1-pentanol, and 1.40 g of linseed oil (Zheng et al 2011(Zheng et al , 2012a. The precursor was gently mixed with 80.00 g of deionized water or seawater to obtain microemulsion with a concentration of 20 % (w/w).…”
Section: Microemulsion Preparation and Its Stability Investigationmentioning
confidence: 99%
“…In addition, the addition of alcohol further enhances contaminants' solubilization by lowering the surface tension between the surfactant tails and the oil (Testard and Zemb 1998). It is already revealed that, in microemulsions, oil provides hydrophobic cores for solubilizing hydrophobic contaminants, while the interfacial film formed by alcohol and surfactant can stabilize the microemulsion system and meanwhile increase the degree of solubilization of hydrophobic contaminants (Zheng et al 2011(Zheng et al , 2012a. Thus, microemulsions have some special properties including ultralow interfacial tension between the oil and water phases, larger interfacial area, and higher solubilizing capacity for hydrophobic compounds over surfactant solutions (Zheng et al 2011(Zheng et al , 2012a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation